Race : a philosophical introduction - Taylor, Paul C. (Paul Christopher), 1967- (Cambridge, UK ; Medford, MA : Polity Press, 2022)
'Every perspective on the philosophy of race explained accessibly'--
The language of race -- Unnatural histories -- Three challenges to race-thinking -- What races are: twenty questions about racial metaphysics -- Ethics, existence, experience -- The color question -- A funny thing happened on the way to post-racialism.
Includes bibliographical references and index.
Keywords: Race -- Philosophy; Race relations -- Philosophy